Thomson Engineering guide to web research 2007-2008 - Heckman, Grant (Thomson Engineering, 2008)
A concise, practical guide to conducting web research for undergraduate students, the Thomson Engineering Guide to Web Research 2007-2008 is the prefect compliment to any course that requires students to navigate the online environment for information. Small, portable, and affordable this versatile product stands on its own but can be packaged to augment any text or course where instructors want to help their students succeed